Clathrin-mediated endocytosis regulates fMLP-mediated neutrophil polarization. Issue 9 (September 2018) - Tan, Xinyu; Luo, Mingzhi; Liu, Allen P.
Abstract: A cell's ability to establish polarization is one of the key steps in directional migration. Upon the addition of a chemoattractant, N-formylmethionyl-leucyl-phenylalanine (fMLP), neutrophils rapidly develop a front end marked by a wide and dense actin network which is a feature of cell polarization. Despite a general understanding of bi-directional crosstalk between endocytosis and polarization, it remains unclear how clathrin-mediated endocytosis (CME) induced by chemoattractant binding to formyl peptide receptor (FPR) affects neutrophil polarization. In this work, we characterized the spatial organization of FPR and clathrin-coated pits (CCPs), the functional unit of CME, with and without fMLP and found that fMLP induced different distributions of FPR and CCPs. We further found that cells had impaired polarization induced by fMLP when CME is inhibited by small molecule inhibitors. Under these conditions, pERK, pAkt308, and pAkt473 were all severely blocked or had altered dynamics. The spatial organization between actin and two major clathrin-mediated endocytic proteins, clathrin and β-arrestin, were distinct and supported clathrin and β-arrestin's functional roles in mediating neutrophil polarization. Together these results suggest that CME plays a pivotal role in a complex process such as cell polarization.